RITUAL COMMUNICATION IN THE TRADITION OF NGASUH GUMI EFFORTS TO REJECT BALA AMONG THE PEOPLE OF TANJUNG DISTRICT, NORTH LOMBOK REGENCY - Sarjono; Agus Dedi Putrawan; Kadri (TASAMUH, 2022)
This research examines the practice of ritual communication in the ngasuh gumi tradition and the meaning of the ngasuh gumi tradition in the Tanjung District community. This study aims to determine the stages of the ritual communication process in the ngasuh gumi tradition, as well as the meaning of the ngasuh gumi ritual for the people of Tanjung District. In other words, the research is aimed at describing the process of implementing the ngasuh gumi ritual through the lens of ritual/transcendental communication theory. This research includes qualitative research with an ethnographic approach to communication. The data collection technique is carried out with interviews and field observations. The results showed that ritual communication practices in the ngasuh gumi tradition include communication that means gathering, friendship, and ownership of common beliefs; the process that occurs in ritual communication is not centered on the transmission of information, but rather prioritizes sharing about common culture; communication is a sacred and sacred activity; the use of language in ritual communication is carried out artificially and symbolically; and it requires communicants to take part jointly